PERLINDUNGAN HUKUM TERHADAP PEMEGANG SAHAM MINORITAS DALAM UNDANG-UNDANG PERSEROAN TERBATAS DALAM KAITANNNYA DENGAN PELAKSANAAN PRINSIP GOOD CORPORATE GOVERNANCE: STUDI ATAS PERUSAHAAN PENANAMAN MODAL ASING (KERJASAMA JOINT VENTURE) - Binoto Nadadap; Bernard Nainggolan; Setyo Sardjono (to-ra, 2021)
Foreign investment must be in the form of a Limited Liability Company as stipulated in article 5 paragraph 1 of law No.25 of 2007 concerning Investment, so that a Joint Venture Company which is also a form of foreign investment, in addition to referring to the investment regulations, is also subject to the rules. regarding Limited Liability Companies. The Limited Liability Company Law has also implemented the principles of Good Corporate Governance (GCG) so that it can be concluded that Joint Venture Companies have also implemented GCG principles in their company's operational activities. The Limited Liability Company Law also regulates the rights of shareholders as mandated by the principles of Good Corporate Governance (GCG). Kata kunci : Perlindungan Hukum, Penanaman Modal Asing, Joint Venture, Good Corporate Governace, Pemegang Saham Minoritas.